The Implementation of Restorative Justice in Overcoming Prison Overcapacity is Reviewed from the Criminal Procedure Law (Cirebon Class I Prison Study) - Aldi, Ahmad; Herdyanto , Jovano Kevin; Purwanto , Ilham; Harmono , Harmono; Harliyanto , Rois (Journal of Legal and Cultural Analytics, 2025)
The high rate of overcapacity in correctional institutions in Indonesia is a structural problem that has multidimensional impacts, ranging from a decline in the quality of inmate coaching to human rights violations. One of the main reasons is the still-dominant imprisonment-based criminal paradigm, including for minor crimes. To find a more humane and efficient solution. The restorative justice approach, as regulated in the National Police Regulation of the Republic of Indonesia Number 8 of 2021, has begun to be implemented in the criminal justice system. This study aims to analyze the normative conformity between the Perpol and the Criminal Procedure Code (KUHAP) and evaluate the effectiveness of restorative justice in reducing the burden on prison inmates, especially in Cirebon Class I Prison. This study employs a mixed-method approach, combining normative juridical and empirical juridical methods. The study results show that although there is a potential disharmony between Perpol and the Criminal Procedure Code, applying restorative justice has provided room for resolving cases more adaptive to restorative justice, especially in minor cases. A study at the Cirebon Police shows that the settlement of five cases through restorative justice in 2025 directly contributes to the prevention of imprisonment and reduces the potential for overcapacity. In Cirebon Class I Prison, an overcapacity of 82.88% was recorded, with most inmates coming from general crimes that have the potential to be resolved through non-litigation mechanisms. Restorative justice is an essential instrument in reforming the penal system, which not only restores social relations but also enhances the efficiency of law enforcement. To achieve long-term effectiveness, it is essential to strengthen legislative regulations and promote synergy among law enforcement institutions.